Subcutaneous retrograde migration of a distal catheter in a ventriculoperitoneal shunt system: presentation of 5 cases - Blanco, Rodrigo Alberto; Pascuetín, Gisela M.; Giustiniano, Lucio; Pérez Zabala, Joaquín; Gromadzyn, Guido; Pirozzi Chiusa, Christian (Revista Argentina de Neurocirugía, 2026)
Background: hydrocephalus is a common condition in neurosurgical practice. Although the placement of a ventriculoperitoneal shunt (VPS) has significantly improved patient outcomes, the procedure is not without complications. Among these, subcutaneous retrograde migration of the distal catheter is a rare event, with few cases reported in the literature. Objectives: to present a series of cases of subcutaneous retrograde migration of the distal catheter in ventriculoperitoneal shunt systems, describe their clinical and imaging characteristics, and propose a surgical strategy for their management. Case description: we present five patients with suspected valvular dysfunction due to clinical signs of intracranial hypertension. They were evaluated using an imaging protocol that showed dilatation of the ventricular system and retrograde migration of the distal catheter in all cases. The tip of the catheter was located outside the peritoneal cavity, manifested on imaging as the "shotgun barrel sign" and "fishing hook sign." Based on these findings, surgical revision of the shunt system was indicated. Surgery: surgical approach and revision exclusively of the distal or abdominal segment of the shunt system, followed by reintroduction of the distal catheter into the peritoneal cavity, achieving secure closure and securing the catheter with a purse-string suture technique. Conclusion: retrograde migration of the distal catheter in ventriculoperitoneal shunts is a rare complication that presents characteristic features in routine studies and is easily detectable. This study proposes a surgical alternative to conventional revision, with multiple benefits and optimal outcomes.